THE REGISTER USED BY THE WORKERS OF PT. MULTI DUTA UTARI. - Tias Arilah; WIjayadi Wijayadi; Waode Hamsia (Tell : Teaching of English Language and Literature Journal, 2017)
This study is sociolinguistics. It focuses on register used by the workers of PT. Multi Duta Utari. In productionDepartment, workers in PT. Multi Duta Utari, used register in context with their occupation. They use registerwhen they communicated in location production department of PT. Multi Duta Utari. The data taken are from inthe two statements, there are what are the type of the register used by the workers of PT. Multi Duta Utari, andwhy do the workers use such as the register. There are the objectives of the study that must be answered: (1)Toidentify the registers used by the workers in company of PT. Multi Duta Utari (2)To describe the reasons whythe workers use such registers. This study used a descriptive qualitative method. The data are collected from thesources including the subject and the place from the collecting data analysis, and triangulation. Finally, thewriter hopes that the finding will be useful to enrich our insight of sociolinguistics.